2015
DOI: 10.18632/oncotarget.3127
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage depletion reduces postsurgical tumor recurrence and metastatic growth in a spontaneous murine model of melanoma

Abstract: Surgical resection of tumors is often followed by regrowth at the primary site and metastases may emerge rapidly following removal of the primary tumor. Macrophages are important drivers of tumor growth, and here we investigated their involvement in postoperative relapse as well as explore macrophage depletion as an adjuvant to surgical resection. RETAAD mice develop spontaneous metastatic melanoma that begins in the eye. Removal of the eyes as early as 1 week of age did not prevent the development of metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 44 publications
2
34
0
Order By: Relevance
“…In a chemically induced mouse model of lung adenocarcinoma, depletion of TAMs reduced tumor growth as a result of down-regulation of M2/TAM recruitment, possibly due to the inactivation of CCL2/CCR2 signaling (Fritz et al, 2014). Likewise, depletion of M2 macrophages in various murine tumor models including cutaneous T cell lymphoma (Wu et al, 2014), colon cancer, lung cancer, breast cancer (Luo et al, 2006) and melanoma (Ries et al, 2014; Ruffell et al, 2014; Tham et al, 2015) have shown similar results. Several reports have discussed the role of macrophages in mediating therapeutic resistance in cancer (De Palma and Lewis, 2013; Ruffell et al, 2014; Ruffell and Coussens, 2015).…”
Section: Tumor Cell-extrinsic Factors For Primary and Adaptive Resistmentioning
confidence: 78%
“…In a chemically induced mouse model of lung adenocarcinoma, depletion of TAMs reduced tumor growth as a result of down-regulation of M2/TAM recruitment, possibly due to the inactivation of CCL2/CCR2 signaling (Fritz et al, 2014). Likewise, depletion of M2 macrophages in various murine tumor models including cutaneous T cell lymphoma (Wu et al, 2014), colon cancer, lung cancer, breast cancer (Luo et al, 2006) and melanoma (Ries et al, 2014; Ruffell et al, 2014; Tham et al, 2015) have shown similar results. Several reports have discussed the role of macrophages in mediating therapeutic resistance in cancer (De Palma and Lewis, 2013; Ruffell et al, 2014; Ruffell and Coussens, 2015).…”
Section: Tumor Cell-extrinsic Factors For Primary and Adaptive Resistmentioning
confidence: 78%
“…Accordingly, intraocular models of melanoma in syngeneic mice showed a tumor-promoting role of M2 type macrophages, particularly in aged mice [264, 265]. Indeed, depletion of macrophages strikingly inhibited intraocular melanoma growth in a syngeneic model [264] and, more recently, in a transgenic model of UM [266]. Expression of M1/M2 polarization genes is strongly associated with metastatic risk [223].…”
Section: Inflammationmentioning
confidence: 99%
“…These MT-ret/AAD mice are suitable for analyzing CD8+ T cell responses directed against immunogenic antigens found in HLA-A2+ melanoma patients [394]. This model allowed establishing the pro-metastatic effects of macrophages, which could be abrogated by treatment with the CSF-1R-specific kinase inhibitor Ki20227 [266]. In another study, the effect of the pro-inflammatory and autoimmune background of the non-obese diabetic (NOD) strain was assessed by back-crossing MT-ret with NOD mice, which resulted in rapid UM development.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Tumorospheres and the multicellular tumor spheroid (MTS) model were cultured in a serum‐free system as previously described . Third‐generation/tertiary suspension cells were used for all subsequent experiments.…”
Section: Methodsmentioning
confidence: 99%